Psychological theories of car use: An integrative review and conceptual framework. (February 2018) - Chng, Samuel; Abraham, Charles; White, Mathew P.; Hoffmann, Christin; Skippon, Stephen
Abstract: Personal car use is increasing globally and is an important contributor to poor air quality and global greenhouse gas emissions. Although individuals have little direct control over some emission sources (e.g. heavy industry), they can modify their car use thereby reducing their own contribution. There have been many attempts to understand the psychology of personal car use and identify ways in which individuals might be encouraged to adopt more environmentally friendly travel modes. The aims of this study were (1) to review available psychological theories and models and their applications to understanding car use, (2) to assess the quality of empirical tests of relevant theories and (3) to develop an integrated conceptual overview of potentially modifiable antecedents that could inform future intervention design and further theoretical research. Fifteen psychological theories were identified from thirty-two unique studies but most theories were applied only once. Although two theories in particular (the Comprehensive Action Determination Model and Stage Model of Self-Regulated Behaviour Change) are both relatively comprehensive and have empirical support, our review suggests there are mechanisms of behavioural regulation relevant to car use that are not included in either theory. Integrating theories, we developed an integrative conceptual framework, referred to as the CAr USE (or CAUSE) framework of cognitive and emotional antecedents of car use. This framework is likely to be applicable to other ecologically-relevant behaviour patterns. Implications for research and practice are discussed. Highlights: Psychological theories were reviewed to better understand modifiable antecedents of car use. Comprehensive theories of how and why environmental behaviour patterns are initiated and sustained have been developed. However, some mechanisms underlying car use choice are not represented in theory and have not been empirically investigated. An integrated conceptual overview of car use based on multiple theories is presented. The framework highlights the complexity of antecedents of car use and related environmental behaviours.